Assessing Climate Impact: Distribution Modeling and Conservation Assessments of Sesamum (Pedaliaceae) Species - Daniel A. Zhigila; Nawal Shrestha; Zainab A. Abubakar; A. Muthama Muasya (Ecology and Evolution)
ABSTRACT Plants with restricted distributions and small population sizes are particularly vulnerable to climate change. Sesamum species are ideal for species distribution modeling due to their ecological sensitivity, agricultural and economic importance, and wide geographic range, providing insights for conservation and policy. We applied the maximum entropy (MaxEnt) model to assess the global ecological niche breadth of Sesamum species and examine how bioclimatic and soil variables influence their future (2080) distribution. We identified key environmental drivers and projected species‐specific range shifts under changing climatic conditions. MaxEnt models effectively predicted suitable habitats, with climate variables playing a dominant role. Precipitation of the wettest month (BIO13) was particularly influential for S. abbreviatum, S. alatum, and S. angustifolium, while temperature variables (BIO7, BIO11) were also key. Elevation moderately impacted S. angolense, while soil factors such as pH (S. abbreviatum) and clay content (S. angolense) exhibited species‐specific effects. Principal component analysis revealed variation in niche breadth, with S. indicum and S. schinzianum occupying broader ecological ranges, whereas S. saxicola and S. abbreviatum were more restricted. Future projections suggest 46.4% of the species will experience range contractions, with S. schinzianum facing the most significant decline. Conversely, 39.3% of the species, including S. imperatricis and S. abbreviatum, are expected to expand their ranges. Phylogenetic analyses indicate a random distribution of niche breadth and extinction risk across the genus. Our findings highlight the susceptibility of Sesamum species to climate change, emphasizing the need for urgent conservation actions. Prioritizing vulnerable species such as S. forbesii and S. sesamoides, alongside habitat restoration and long‐term monitoring, is crucial to mitigate population declines and prevent extinction.